Propaganda and Journalism (in the Context of the Second Karabakh War) - Kosiuk, Oksana M. (Europe Our House, Tbilisi, 2022)
Propaganda has always existed; it only changed its forms. In the early days of media it first flooded the pages of popular periodicals and later when the media improved and clearly outlined their boundaries on the basis of international standards it became in opposition to journalism and was legally circulated without obstacles exclusively in party and religious media. Therefore it is regarded in journalism as a negative manifestation of fake creativity and gross evidence of information imbalance. However, has this ambivalent phenomenon really disappeared “law abidingly” from leading mass media and consequently what effect has it had on public consciousness and national security of states which are in zones of military confrontation? We are answering the abovementioned and similar questions in the article through the example of the analysis of key mass media in Azerbaijan, Armenia, Russia and Ukraine. Mediation of the conflict in Nagorhy Karabakh was purposefully chosen as the objective of scientific receptions but not the war in eastern Ukraine as it could be reasonable to expect with the aim to abstract ourselves from personal views and experiences and check objectively if there is any propaganda and how it works in the coverage of global military conflicts that directly or indirectly affect certain states. It was equally important to investigate whether the implementation of information standards contributes to settlement of intra-state and international confrontations. It has been found out that compliance with media norms is in inverse proportion to national interests. Finding a way out of these clear-cut situations opens up prospects for new research.
Keywords: Nagorhy Karabakh; propaganda; ideology; media; armed conflict; state; information war